Eye Diseases: When the Solution Comes from Plant Alkaloids - Lorrai, Riccardo; Cavaterra, Dario; Giammaria, Sara; Sbardella, Diego; Tundo, Grazia Raffaella; Boccaccini, Alessandra (Planta Medica, 2024)
Plants are an incredible source of metabolites showing a wide range of biological activities. Among these, there are the alkaloids, which have been exploited for medical purposes since ancient times. Nowadays, many plant-derived alkaloids are the main components of drugs used as therapy for different human diseases. This review deals with providing an overview of the alkaloids used to treat eye diseases, describing the historical outline, the plants from which they are extracted, and the clinical and molecular data supporting their therapeutic activity. Among the different alkaloids that have found application in medicine so far, atropine and pilocarpine are the most characterized ones. Conversely, caffeine and berberine have been proposed for the treatment of different eye disorders, but further studies are still necessary to fully understand their clinical value. Lastly, the alkaloid used for managing hypertension, reserpine, has been recently identified as a potential drug for ameliorating retinal disorders. Other important aspects discussed in this review are different solutions for alkaloid production. Given that the industrial production of many of the plant-derived alkaloids still relies on extraction from plants, and the chemical synthesis can be highly expensive and poorly efficient, alternative methods need to be found. Biotechnologies offer a multitude of possibilities to overcome these issues, spanning from genetic engineering to synthetic biology for microorganisms and bioreactors for plant cell cultures. However, further efforts are needed to completely satisfy the pharmaceutical demand.
Keywords: plant alkaloids; retinal disease; plant metabolites; myopia; diabetic retinopathy